Comportamento sexual e reprodutivo de mulheres indígenas no Alto Xingu, Mato Grosso, Brasil - Madeira, Sofia Pereira [UNIFESP] (2015)
Historically, due to contact with colonizing fronts and economic expansion, indigenous peoples have experienced significant population loss, feeding pessimistic forecasts that pointed their disappearance. However, many indigenous peoples in Brazil are in the process of demographic recovery, growing more than the average of the population in recent decades due to high fertility rates among women of the group. This scheme is the result of cultural norms that regulate the size of families according to strategic needs of power and occupation of territories, aiming the operation of their complex systems of social organization. For this, they resort to deliberate practices to encourage and/or limitation of births - depending on the historical, cultural, political and economic context - such as age at marriage, postpartum sexual abstinence, abortions and late practices of birth control. However, the presence and the performance of health teams subsidized by the government or by the Academy within the Alto Xingu communities - where is the target population of this study - appear to inhibit the reporting of certain traditional practices that are doomed from the perspective of brazilian society. Researchers are faced with ethical limits by displaying knowledge of the continuity of these practices, since informants refuse to accept the maintenance of certain customs, such as abortion and late practices of birth control. This apparent inconsistency between theory and practice makes us reflect on the ethical limits of researchers and health professionals in dealing with traditional peoples, in view of the embarrassment and the limitation of sexual and reproductive rights of women of these communities and also reflect on the anthropologist?s place during fieldwork.